Learning Transformation: The Application of Augmented Reality Media to Improve Motivation and Interest in Learning Among Elementary School Students in the 5.0 Era - Asiah, Nur; Lakilaki, Eogenie; Khusnadin, Muhammad Hafidz; Eprilia, Winda; Negara, Hasan Sastra; Rizky, Muhammad (Universitas Syiah Kuala, 2025)
The integration of Augmented Reality (AR) media in education has emerged as a promising approach to enhance engagement and motivation among elementary students in the 5.0 Era. This study investigates the dual impacts of AR on student motivation and interest in learning. Employing a Classroom Action Research (CAR) method, the research was conducted in a cyclical process of planning, action, observation, and reflection over four weeks at SDN XX Palembang, targeting sixth-grade students. A stratified random sampling method was used to select the participants. Data were collected through weekly surveys to quantitatively measure motivation and interest levels, and through direct observations and interviews to provide qualitative insights. The findings reveal a significant and consistent increase in both motivation and interest scores, with motivation rising from an average of 35.2 to 71.2 and interest from 33.7 to 72.3. Qualitative data corroborated these results, showing a transformation in student behavior from initial curiosity to collaborative problem-solving and independent learning. The study concludes that AR is a transformative and sustainable pedagogical tool that effectively fosters a dynamic and student-centered learning environment. This research provides a valuable model for educators seeking to integrate technology to enhance learning experiences